SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Admixture Affects the Rate and Repeatability of Experimental Adaptation to a Stressful Environment in Callosobruchus maculatus - Amy Springer; Brian Kissmer; Zachariah Gompert (Molecular Ecology, 2025)
Hybridisation and admixture are common in nature and can serve as important sources of adaptive potential by generating novel genotype combinations and phenotypes. However, hybrid incompatibilities can also reduce hybrid fitness. Given the pervasiveness of admixture and its potential role in facilitating adaptation, understanding how admixture influences the rate and repeatability of evolution is critical for advancing our understanding of evolutionary dynamics. Yet, few studies have examined how patterns of evolutionary repeatability in admixed lineages are shaped by strong ecological pressures. In this experiment, we evaluated patterns of evolution and repeatability in admixed and non‐admixed cowpea seed beetles ( Callosobruchus maculatus ) adapting to a novel, stressful host: lentil. Specifically, we asked (1) whether admixture facilitates adaptation to lentil, (2) whether repeatability is greater in admixed or non‐admixed lineages, and (3) to what extent repeatability in admixed lineages is driven by selection on globally adaptive alleles versus epistatic effects and hybrid incompatibilities. We found that admixture facilitated adaptation to lentil, and evolutionary rescue–defined as adaptation that prevents population extinction–occurred in all lineages. Evolutionary repeatability was highest in two admixed lineages, though evident across all lineages. Adaptation to lentil appeared largely driven by selection on globally adaptive alleles. Nevertheless, even under conditions of evolutionary rescue in a marginal environment, the purging of hybrid incompatibilities contributed substantially to repeated evolution in admixed lineages.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Considerable genetic diversity and structure despite narrow endemism and limited ecological specialization in the Hayden's ringlet, Coenonympha haydenii - Amy L. Springer; Zachariah Gompert (Molecular Ecology, 2024)
Understanding the processes that underlie the development of population genetic structure is central to the study of evolution. Patterns of genetic structure, in turn, can reveal signatures of isolation by distance (IBD), barriers to gene flow, or even the genesis of speciation. However, it is unclear how severe range restriction might impact the processes that dominate the development of genetic structure. In narrow endemic species, is population structure likely to be adaptive in nature, or rather the result of genetic drift? In this study, we investigated patterns of genetic diversity and structure in the narrow endemic Hayden's ringlet butterfly. Specifically, we asked to what degree genetic structure in the Hayden's ringlet can be explained by IBD, isolation by resistance (IBR) (in the form of geographic or ecological barriers to migration between populations), and isolation by environment (in the form of differences in host plant availability and preference). We employed a genotyping‐by‐sequencing (GBS) approach coupled with host preference assays, Bayesian modelling, and population genomic analyses to answer these questions. Our results suggest that despite their restricted range, levels of genetic diversity in the Hayden's ringlet are comparable to those seen in more widespread butterfly species. Hayden's ringlets showed a strong preference for feeding on grasses relative to sedges, but neither larval preference nor potential host availability at sampling sites correlated with genetic structure. We conclude that geography, in the form of IBR and simple IBD, was the major driver of contemporary patterns of differentiation in this narrow endemic species.

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Genomic time‐series data show that gene flow maintains high genetic diversity despite substantial genetic drift in a butterfly species - Zachariah Gompert; Amy Springer; Megan Brady; Samridhi Chaturvedi; Lauren K. Lucas (Molecular Ecology, 2021)
Effective population size affects the efficacy of selection, rate of evolution by drift and neutral diversity levels. When species are subdivided into multiple populations connected by gene flow, evolutionary processes can depend on global or local effective population sizes. Theory predicts that high levels of diversity might be maintained by gene flow, even very low levels of gene flow, consistent with species long‐term effective population size, but tests of this idea are mostly lacking. Here, we show that Lycaeides butterfly populations maintain low contemporary (variance) effective population sizes (e.g. ~200 individuals) and thus evolve rapidly by genetic drift. However, populations harboured high levels of genetic diversity consistent with an effective population size several orders of magnitude larger. We hypothesized that the differences in the magnitude and variability of contemporary versus long‐term effective population sizes were caused by gene flow of sufficient magnitude to maintain diversity but only subtly affect evolution on generational timescales. Consistent with this hypothesis, we detected low but nontrivial gene flow among populations. Furthermore, using short‐term population‐genomic time‐series data, we documented patterns consistent with predictions from this hypothesis, including a weak but detectable excess of evolutionary change in the direction of the mean (migrant gene pool) allele frequencies across populations and consistency in the direction of allele frequency change over time. The documented decoupling of diversity levels and short‐term change by drift in Lycaeides has implications for our understanding of contemporary evolution and the maintenance of genetic variation in the wild.

Species collisions, admixture, and the genesis of biodiversity in poison frogs - Amy Springer; Zachariah Gompert (Molecular Ecology, 2020)

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)